Diversity of terrestrial ferns (Pteridophytes) in Ciliwung Telaga Warna Puncak Bogor tea estate in West Java. Issue 1 (April 2021) - Wiranto, Basar; Husnin,; Susilo,
Abstract: Very few research has been done on the diversity of terrestrial ferns (Pteridophyta) in the Ciliwung Telaga Warna Puncak tea garden in Bogor, West Java. This research aims to understand the diversity of ferns and species of ferns found in the tea plantation area of Ciliwung, Telaga Warna Puncak, Bogor, West Java, by examining ecological indices in the form of important value index and diversity index. Objects collected in the observation were all types of ferns in the Ciliwung Telaga Warna Puncak tea plantation area, Bogor, West Java through line transect techniques (transect sampling) and rectangular sampling which were placed randomly in the census zone (sampling square). The data obtained were processed quantitatively with Microsoft Excel. From the research conducted in the Ciliwung Telaga Warna tea plantation area, 18 species were found. The highest index of important value for ferns was Selaginella sp, at 92.98% and the lowest was Lycopodiella cernua with an INP value of 1.15%. The value of H'(Species Diversity) obtained in the Ciliwung Telaga Warna Puncak tea plantation area with 4 transects and 100 plots was 1.425, indicating that the species diversity on a transect was moderate.